Transient Well Performance Modeling for Reservoir Pressure Determination - Hon, Vai Yee (2010)
Continuous reservoir pressure data acquisition through intrusive well intervention has always been a challenge to the industry due to a combination of economic, operational and logistical constraints. This paper presents an alternative methodology wherein the reservoir pressure can be computed from the well’s steady-state flow properties and wellhead shut-in data using an advanced transient well algorithm.